Lexical chunks for promoting explicit learning vocabulary - Tandalla Chicaiza, Elver Rolando (2016)
The present research project was developed to determine the explicit learning vocabulary with lexical chunks through a literature review in order to promote reading in students. The problem involves that students have lack of vocabulary for understanding written paragraphs in the English language, causing lack of understanding words and simple phrases from the English book due to vocabulary is an important part for understanding a foreign language. Then, if leaners have shortage of vocabulary, they cannot understand the part of reading and writing communication. To develop this research, it was applied research methodologies such as descriptive method that helps to recollect, interpret, analyse, and discuss data. That is why, it was used instruments as surveys that were guided to the students of 10th grade of basic education at “Semillas de Vida” Educative Unit….